Agen Ganda dan Perubahan Praktik Pertanian - Firdaus Marbun (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2021)
This article aims to explain the role of dual agents in bringing about changes in agricultural practices.  Starting from the phenomenon of changing plant species that occurred in Parbotihan Village, Onan Ganjang District, Humbang Hasundutan Regency.  Changes in these types of crops often occur in a short period of time and are followed by most farmers.  These changes sometimes occur without considering the adequacy of land, cultivation knowledge, and capital capacity.  So, often the changes that occur are not profitable for them.  On the other hand, these changes also change the cultivation pattern which requires farmers to learn from the beginning as a consequence of changing the types of plants.  This research was conducted during the research period of my thesis by collecting data through observation and interviews. The selected informants are farmers who are involved in changing practices. The author found that the role of multiple agents such as relatives, friends, skippers, and group leaders with different capacities had a role in influencing farmers' actions. Multiple agents act as initiators, motivators, introductors, educators, and interventors. This research also shows that the social arena as public space becomes an effective arena in exchanging information and influences that encourage practice change.